Composition and quality of fresh cow milk offered for sale in Obudu Grass Plateau, Cross River State – Nigeria - Anya, M. I.; Ozung, P.O. (Nigerian Journal of Animal Science, 2023)
The chemical composition and quality of fresh cow milk from Fulani milk vendors in four locations (Utal –ugar, Anape, Gundaha and Keyi) of Obudu grass Plateau–Cross River State were investigated. Methylene blue dye reduction test was used to assess the milk quality while the bacterial load (contamination) was assessed using the agar plate count and the direct microscopic counts. The results showed mean contents of total solids, protein, butterfat, ash and lactose of 160 samples from Utal-ugar (12.78, 5.74, 5.52, 7.26, 0.11, 1.41%), Anape (12.72, 5.71, 5.55, 7.17, 0.13, 1.33%), Gundaha (12.21, 5.98, 4.95, 7.26, 0.16, 1.12) and Keyi (12.34, 5.88, 4.98, 7.36, 0.17, 1.31%) respectively, which did not differ (P>0.05) significantly between locations. The methylene blue reduction for the various locations were 27.5, 40, 32.5; 35, 37.5, 27.5; 15, 47.5, 37.5; 22.5, 42.5, 35% for good, fair and poor samples respectively. No sample merited average or excellent rating. The agar plate count showed a range of 1.95 x106 for Utal-ugar to 2.84 x106 for Gundaha. The direct microscopic count showed the highest mean bacteria load for Gundaha samples. The high bacterial counts observed were probably indicative of poor milking hygiene and handling. The study concludes that fresh milk sold at the Obudu grass plateau by the Fulani milk vendors may not be 100% wholesome. It is proper that such milk be pasteurized before consumption and the vendors urged to deliver their milk to markets early at source to reduce the time for microbial build-up.